Red Soils from Various Parent Materials in Indonesia: The Prospect and Their Management Strategic - PRASETYO, B.H (Indonesian Center for Agriculture Land Resource Development, 2009)
Distribution of red soils is about 50 million hectares, and generally potential for agricultural development in Indonesia. The soil was formed from various parent materials, such as andesitic-basaltic rock, acid tuff, limestone, ultra mafic rock, clay stone and sand stone. Generally the red soils were very developed soils, so that the sand mineralogy was dominated by minerals thatresistent to weathering such as quartz and opaque. The clay mineral was dominated by variable charge minerals which depends on pH like kaolinite followed by gibbsite, goethite, and hematite. These soils have very acid to slightly alkaline reaction, low exchangeable bases, low to high cation exchange capacity, and positive correlation to organic-C in the soil. The red soils according to Soil Taxonomy system could be classified as Inceptisols, Alfisols, Ultisols, and Oxisols. Characterization of the red soils areneeded before they are utilized for agriculture.